Quality of Financial Reporting on UMKM Perpetrators in Bondowoso District - Andrea Meita Gustina; Retno Endah Supeni; Achmad Hasan Hafidzi (Jurnal Sinar Manajemen, 2024)
An optimal level of financial reporting quality is essential to an enterprise, especially Micro, Small and Medium Enterprises (MSMEs). Through good quality financial statements, UMKM can make it easier to plan and make future decisions; a good financial report provides the data necessary for business planning and decision-making. UMKMs can design growth strategies, identify investment opportunities, and address financial challenges with a strong information base. In addition, UMKM can also be easier in obtaining access to funding from financial institutions, which tend to lend to UMKM that can provide a good picture of their financial health. In this study, the researchers conducted a quantitative descriptive survey of 100 UMKM perpetrators responsible for managing financial reports in the Bondowoso district. From the perspective of this research, it is seen that most of the 100 criminals/owners of UMKM in the Bondowosos district have an excellent human resources account and financial literacy. However, many still have not used information technology. The results of the double regression analysis showed the positive impact of human resource competence, financial literacy, and the use of information technology on the quality of financial statements.